Hepatic cyst infection in a healthy older male. (20th March 2012) - Mori, Eiichiro; Akai, Yasuhiro; Matsumoto, Takaki; Kawaratani, Hideto; Horii, Manabu; Iwano, Masayuki; Uemura, Shiro; Nonomura, Akitaka; Fukui, Hiroshi; Saito, Yoshihiko
Abstract : Simple hepatic cysts are usually asymptomatic and are not associated with impaired hepatic function. However, complications, such as obstructive jaundice, rupture, intracystic haemorrhage and infection, can occur. The authors describe the case of a 82-year-old man with fever and elevated C-reactive protein. A repeat contrast-enhanced abdominal CT scan revealed enlargement with peripheral enhancement in the left lateral segment of the liver. A diagnosis of infected hepatic cyst was made, and percutaneous transhepatic drainage of the cyst was performed. When a patient has liver cysts and high-grade fever, liver cysts should be considered as a focus of infection. Repetition of ultrasonography and/or CT studies should be considered, even if no typical findings are obtained initially. It is of note that conventional Ga-scintigraphy may be useful for the detection of infected site.